The Effect of Efficiency, Effectiveness, and Financial Leverage on The Performance of Public Companies in Automotive Sub-Sector - Yonathan Reinhard; Maswar Abdi (International Journal of Application on Economics and Business, 2023)
The goal of the company is to maximize the value of the owner's wealth. The success of the company will be seen through the financial performance. The financial performance is measured through Return on Equity (ROE). According to Du Pont's theory, the company's ROE is influenced by efficiency, effectiveness and financial leverage. The purpose of this study is to determine the effect of efficiency, effectiveness and financial leverage to the performance of public companies. The population in this study are all public companies in the automotive sub-sector between the year of 2016 until 2020 with the sample of 10 automotive companies. This study uses multiple linear regression analysis with the help of EViews 10 software. The results of this study indicate that (1) operational efficiency has a negative and significant effect on company performance, (2) the effectiveness of asset use has a positive and significant effect on company performance, (3) financial leverage has a negative but not significant effect on company performance.